Heart failure risk prediction and medicine recommendation system using exploratory analysis and big data analytics - Habib, Sumaya; Moin, Maisha Binte; Aziz, Sujana (BRAC University, 2019)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2018.